The mediating effect of green innovation on the relationship between green supply chain management and environmental performance - Abu Seman, Noor Aslinda; Govindan, Kannan; Mardani, Abbas; Zakuan, Norhayati; Mat Saman, Muhamad Zameri; Hooker, Robert E.; Ozkul, Seckin (Elsevier, 2019)
The emerging environmental awareness of the public, as well as the implementation of governmental regulations, force organisations to employ corporate environmental practices such as green supply chain management (GSCM) and green innovation. Accordingly, both practices are crucial to achieve professional improvement in the environmental performance of these organisations. However, research on the relationship of GSCM, green innovation, and environmental performance is relatively rare. Therefore, this study is aimed to provide empirical evidence showing that GSCM and green innovation practices significantly improve environmental performance in order to encourage organisations to implement these practices. In addition, this study investigates the relationship between GSCM and green innovation practices and the influence of these practices on the environmental performance in 123 manufacturing organisations with ISO 14001 certification. The results of PLS-SEM revealed that there is a significant and positive relationship between GSCM and green innovation, and the environmental performance. Moreover, green innovation had a positive effect on the environmental performance. Furthermore, green innovation had a mediating relationship between GSCM and environmental performance. Therefore, the present paper confirmed the significant influence of GSCM on boosting the green innovation of organisations and on the manufacturing establishments, which eventually improve the environment. In brief, the outcomes of this study provide enhanced understanding about the significant role of green innovation in the manufacturers for improving their GSCM and organisational environmental performance.